2018
DOI: 10.1039/c8nr03820a
|View full text |Cite
|
Sign up to set email alerts
|

BN nanospheres functionalized with mesoporous silica for enhancing CpG oligodeoxynucleotide-mediated cancer immunotherapy

Abstract: CpG oligodeoxynucleotides (CpG ODNs) possess strong immunostimulatory activity, which hold great promise in cancer immunotherapy. However, their therapeutic efficacy is largely limited due to nuclease degradation and poor cellular internalization. Efficiently delivering CpG ODNs into target cells is crucial to improve their therapeutic efficacy. Boron nitride nanospheres (BNNS) possess advantage as carriers for CpG ODNs. However, their poor aqueous dispersity and low CpG ODN loading capacity became a big obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The formulation of CpG-ODN with nanoparticles further improves the immune protective effect [30,33,34]. A recent study using boron nitride nanospheres functionalized with mesoporous silica demonstrated enhanced the delivery of CpG ODNs into macrophages that induced higher amounts of cytokines without cytotoxicity [47]. Previous studies suggested that enhanced expression of cytokines and chemokines [34,35] and increased cellular functions, such as the increase in heterophil degranulation and oxidative burst [48], play important roles in CpG-ODNinduced protection in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation of CpG-ODN with nanoparticles further improves the immune protective effect [30,33,34]. A recent study using boron nitride nanospheres functionalized with mesoporous silica demonstrated enhanced the delivery of CpG ODNs into macrophages that induced higher amounts of cytokines without cytotoxicity [47]. Previous studies suggested that enhanced expression of cytokines and chemokines [34,35] and increased cellular functions, such as the increase in heterophil degranulation and oxidative burst [48], play important roles in CpG-ODNinduced protection in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of PTT with immunetherapy involving the incorporation of photothermal agents with immunomodulatory agents has brought some inspiring results 74 , 93 . Enhanced anti-cancer effects have been successfully obtained by the combination of photothermal agents and immune checkpoint blockades 94 and immunoadjuvants 95 - 97 . Recently, Pd NSs were reported as carriers of immunoadjuvant CpG oligodeoxynucleotides by our group 98 .…”
Section: Cancer Therapy Using Pd-based Nanomaterialsmentioning
confidence: 99%
“…HydroxylationHydrogel composite[10]5. CpG oligodeoxynucleotidesGene therapy[22,23]6. Pd and copper (II) phthalocyaninePhototherapy[11,19]2.B 24 N 24 1.…”
Section: Functional Properties and Biomedical Applicationsmentioning
confidence: 99%
“…At the same time, the BNNT@mesoporous silica hydrides for controllable surface zeta potential materials have shown higher suspension ability that facilitated intracellular endocytosis of doxorubicin 21. Moreover, the BNNTs encapsulated drug (curcumin) has found to efficient cellular uptake ability and in vitro release potentiality, which associated predictable anti-inflammatory effects of curcumin 22. Another study provided new insight towards the promising application of adenine-functionalized macromer (A-PPG) with the h-BN system in controlled release drug delivery systems.…”
Section: Functional Properties and Biomedical Applicationsmentioning
confidence: 99%